Sovereign Debt: A Quagmire for Growth and Equity - Lijane, Mamokete (Southern Centre for Inequality Studies (SCIS), 2022)
The recent rise in sovereign debt will have a profound impact on countries’ ability to grow and recover after the Covid-19 pandemic; it will also impact the degree of equity within and between countries. This paper assesses the impact of sovereign debt on efforts to address global inequality and development. Whether through policy constraints or its impact on economic structures, the size, use and composition of sovereign debt can affect whether and how countries grow and the inclusivity of economic growth.
Keywords: Pre-distribution and Ownership; Covid-19 pandemic; Global inequality and development